2014
DOI: 10.7860/jcdr/2014/9822.4929
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy: As a First Line Diagnostic Tool for Infertility Evaluation

Abstract: It was observed that tubal disease was the responsible factor in 62.8% women with primary infertility and 54.8% women with secondary infertility followed by pelvic adhesions in 33% and 31.5%, ovarian factor in 14% and 8.5%, pelvic endometriosis in 9.9% and 6.1% women respectively. Thus tubal factor infertility is still a major cause of infertility in developing countries and its management at an early stage is important to prevent an irreversible damage. At the same time, it also directs which couples would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
4
10
1
Order By: Relevance
“…Recently Jain G et al analysed the results of 203 women, on whom, laparoscopy for the evaluation of infertility was done and observed that tubal disease was the responsible factor in 62.8% women with primary infertility and 54.8% women with secondary infertility followed by pelvic adhesions in 33% and 31.5%, ovarian factor in 14% and 8.5%, pelvic endometriosis in 9.9% and 6.1% women respectively which was consistent with the present study. 29 In contrast to the findings of the present study, Kausar N, et al reported leading causes of infertility as endometriosis and fibroid of the uterus. 30 Other prevalent causes of infertility noted were pelvic inflammatory disease (6.9% in primary infertility and 18.5% in secondary infertility), pelvic tuberculosis (in primary infertility) and polycystic ovaries (46.5% in primary and 30% in secondary infertility).…”
Section: Diagnostic Laparoscopycontrasting
confidence: 99%
“…Recently Jain G et al analysed the results of 203 women, on whom, laparoscopy for the evaluation of infertility was done and observed that tubal disease was the responsible factor in 62.8% women with primary infertility and 54.8% women with secondary infertility followed by pelvic adhesions in 33% and 31.5%, ovarian factor in 14% and 8.5%, pelvic endometriosis in 9.9% and 6.1% women respectively which was consistent with the present study. 29 In contrast to the findings of the present study, Kausar N, et al reported leading causes of infertility as endometriosis and fibroid of the uterus. 30 Other prevalent causes of infertility noted were pelvic inflammatory disease (6.9% in primary infertility and 18.5% in secondary infertility), pelvic tuberculosis (in primary infertility) and polycystic ovaries (46.5% in primary and 30% in secondary infertility).…”
Section: Diagnostic Laparoscopycontrasting
confidence: 99%
“…Our result is similar to the one reported by Mboudou et al who found 71.6% of tubo-peritoneal adhesions among infertile women who underwent laparoscopy in Yaoundé [7]. However, our result is high than 40.6% of pelvic adhesions reported by Mbaye et al among women who underwent laparoscopy at Dakar University Hospital and 33% of pelvic adhesions reported by Jain et al among women who underwent laparoscopy for infertility in India [5] [13]. The difference in the prevalence of pelvic adhesions can be explained by the difference in the characteristics of the study population, in the prevalence of sexually transmitted infection and in the frequency of past history of pelvic surgeries between these studies.…”
Section: Discussionsupporting
confidence: 89%
“…The high incidence of endometriosis observed in infertile women has led many investigators and clinicians to the assumption that there is a causal relationship between these two entities [21]. We identified endometriosis in 13.0% of cases which is close to 9% reported by Jain et al in India among infertile women underwent laparoscopy [13].…”
Section: Discussionsupporting
confidence: 72%
“…These findings establish the role of hysterolaparoscopy in the evaluation of infertility. 9,10 Ovulatory dysfunction is one of the most common cause of infertility accounting 30-40% and Polycystic syndrome (PCOS) being the commonest finding associated with ovulatory dysfunction. 7,11 We report an incidence of 36.63% of patient had ovulatory dysfunction out of which PCOS constitutes 76 (22.82%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of endometriosis is highly variable, varies from 10% to 90%. 10,[13][14][15] In the developing countries due to the high incidences of tuberculosis and pelvic inflammatory disease (PID) up to 39-41% women were associated with infertility. 16 PID causes damage to the fallopian tube along with pelvic adhesions, both leading to impaired tubal function and infertility.…”
Section: Discussionmentioning
confidence: 99%